Strategi Guru, Motivasi Peserta Didik dan Hasil Pembelajaran Tahfizh al-Qur’an di Madrasah Ibtidaiyah Muhammadiyah Teluk Kuantan Singingi - Hendio Anjasmara; Mahyudin Ritonga; Aguswan Rasyid (Universitas Muhammadiyah Sorong, 2021)
This research was conducted to see how teacher strategies, motivation and student learning outcomes in the hifzil Qur'an subject at MI Muhammadiyah Teluk Kuantan. This study was motivated by symptoms in the field such as low motivation of students to memorize the Koran, rarely depositing their memorization and carrying their daily memorization book. This study used a qualitative descriptive approach to see how the teacher's strategy in learning hifzil Qur'an as well as the motivation and learning outcomes of students at MI Muhammadiyah Teluk Kuantan. The results of the research show several things including; MI Muhammadiyah Teluk Kuantan has not implemented the standard strategy used by teachers in learning hifzil Qur'an. The hifzil Qur'an learning strategy that is given to each teacher so that they can adjust and give birth to new innovations in the learning process. The motivation of the next students to follow hifzil Qur'an learning at madrasah was quite good. It is also a scale with learning outcomes dominated by a range of values from 84-92. In fact, most of them also scored above the number 93. Only a few of the students did not complete the hifzil Qur'an learning.